RemarkIf you don't start exactly the right way, you can get into all kinds of trouble. This is just one of those cases. I think the best way to start is to divide both terms by x^(1/2)
Step OneDivide both terms in the numerator by x^(1/2)
y= 6x^(1/2) + 3x^(5/2 - 1/2)
y =6x^(1/2) + 3x^(4/2)
y = 6x^(1/2) + 3x^2 Now differentiate that. It should be much easier.
Step TwoDifferentiate the y in the last step.
y' = 6(1/2) x^(- 1/2) + 3*2 x^(2 - 1)
y' = 3x^(-1/2) + 6x I wonder if there's anything else you can do to this. If there is, I don't see it.
I suppose this is possible.
y' = 3/x^(1/2) + 6x
y' =
Frankly I like the first answer better, but you have a choice of both.
Answer:
- 1/4
- 3/5
Step-by-step explanation:
You find the part by expressing the ratio as a fraction, then simplifying.
1. 5/20 = (1·5)/(4·5) = (1/4)·(5/5) = 1/4
5 is 1/4 of 20.
__
2. 12/20 = (3·4)/(5·4) = (3/5)·(4/4) = 3/5
12 is 3/5 of 20.
7x-8 (2) = 12x+8
14x-16 = 12x+8
-12x -12x
2x-16 = 8
+16 +16
2x = 24
÷2 ÷2
x= 12
UV= 7x-8
UV= 7(12)-8
UV= 84-8
UV= 76
I hope this helps. Have a good day.
Given the equation :
So, to find d , divide both sides by ( -6 )
So,
Note: when we divide two negative numbers, the result will be a positive number